Carbon emissions from urban takeaway delivery in China - Yiqiang Zhong; Shenghui Cui; Xuemei Bai; Wei Shang; Wei Huang; Lingxuan Liu; Shouyang Wang; Rongxuan Zhu; Yuanxiao Zhai; Yin Zhang (npj Urban Sustainability, 2024)
Abstract Online food delivery has become a popular mode of urban food consumption in China as its underlying business mechanism, Online To Offline (O2O), gaining popularity. However, the environmental impacts of a rapidly expanding online food delivery industry and its potential to mitigate environmental burdens remained unexplored in China. Our research found that Chinese cities generated 1.67 MtCO2-equivalent (CO2e) from 13.07 billion times of deliveries in 2019, including transport and packaging. The transportation-related GHG emissions were 745 KtCO2e in 2019, with an average of 0.057 kg CO2e per order and an average of 0.011 kg CO2e per capita. These emissions have surged from 0.31 MtCO2e in 2014 to 2.74 MtCO2e in 2021. We predict that this figure will increase further to 5.94 MtCO2e by 2035. However, with a range of policies such as replacing motorcycles with electric bikes and optimizing traffic routes, it is possible to mitigate such GHG emissions by 4.39–10.97 MtCO2e between 2023 and 2035. These findings highlight the need for further research into the environmental impact of online food delivery and the potential for mitigating it.